Direct compressed tablet with melt dispersed drug particle without binder - Ruzaidi, Ahmad Fahmi; Chatterjee, Bappaditya (2017)
Objective: To prepare ibuprofen tablet without binder by direct compression method. Methodology: Differential scanning calorimetry (DSC), attenuated total reflectance (ATR) and high performance liquid chromatography (HPLC)analysis were done to investigate ibuprofen stability during melting and solidification process as well as compatibility with microcrystalline cellulose (MCC). Ibuprofen was melted at 85 ºC and MCC was dispersed (Ibuprofen: MCC, 1.7: 1 w/w) in molten drug with constant stirring. The dispersion was solidified in an ice bath immediately and then pulverized followed by sieving through 600-micron sieve. The derived powder was tested for flow property and compressibility and compressed into tablet without adding any binder. The prepared tablets were evaluated for hardness, friability, disintegration and in vitro dissolution. Results: No differences in melting peak, enthalpy, functional groups, and chromatographic retention time were observed between ibuprofen and solidified molten ibuprofen. These results indicate heat stability of ibuprofen within the melting range. Compatibility between drug and MCC was also established. The melt dispersed drug powder showed higher bulk density (0.478 g/mL) and Carr index (12.545) compared to physical mixture (ibuprofenMCC). The compressed tablets showed acceptable hardness and friability (less than 1%) as well as acceptable disintegration time (< 30 min). The in vitro dissolution studies showed over 80 % drug release within 30 min. Partial conversion to amorphous nature as well as deformation of crystals by melting and re-solidifying are the reasons of sufficient hardness of the prepared tablet without using binder. Conclusion: Melt dispersed drug particle can be compressed into tablets without binder which will definitely reduce number of inactive ingredients in a tablet and time/cost of preparation. Improved flow property of the drug particles will help to enhance drug loading without granulation. Low melting point and heat stability of the drug at the melting range are desired for adopting such technique.